Penerapan Cahaya Buatan Pada Chamber Semai Tanaman Hidroponik di KWT Sekar Arum - Pratiwi, Artdhita Fajar; Aji, Galih Mustiko; Utami, Sari Widya; Kristiningsih, Ari; Nurhilal, Mohammad (Abdi Panca Marga, 2022)
The limited knowledge owned by KWT Sekar Arum in seedling hydroponic plant seeds and lack of manpower to maintain the seedlings caused the seeds produced to be poor (small stems and few leaf shoots) and some were eaten by pests. Poor seeds produce plants that are not optimal. Therefore, in this community service activity, a nursery chamber is designed for seedling hydroponic plant seeds that utilize solar panel energy as a source of electrical energy in indoor hydroponic plant seed cultivation. This nursery chamber is equipped with artificial light and automatic irrigation so the seedling process can save energy and time. Artificial light is made using 2 types of LED lamps with a red spectrum and a blue spectrum arranged at a certain distance so that the intensity of the light produced is 100 mol/m2/s. To be utilized optimally, all members of KWT Sekar Arum were given counseling and training related to the use of the nursery chamber. In addition, KWT Sekar Arum is also assisted in the process of transplanting and maintaining hydroponic plants so the results are maximized. Based on the results of the evaluation, it can be seen that the transfer of technology provided can be utilized properly by KWT Sekar Arum, the seeds produced from the nursery chamber already have 3-4 leaf shoots when they are 9 days old and ready to transplant, and the results of hydroponic plants produced has been maximized with wide and many leaves.